ACTIVITIES OF EDUCATIONAL SYSTEM IN TURKESTAN DURING RUSSIAN EMPIRE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the influence and significance of schools and educational institutions established during the Russian Empire’s occupation on the development of Uzbekistan’s education system, based on historical evidence. In the introduction, the challenges arising during the Russian Empire’s conquest of Central Asia and the resulting need for a structured education system are analyzed. A comparative analysis approach was applied in evaluating the sources. The study investigates the issue using a chronological sequence, comparative analysis, and regional approach, drawing on archival materials from the republic and regional archives. Specifically, the study focuses on the provinces of the Turkestan General-Governorship, with the Caspian region serving as a primary example. In conclusion, the article discusses the impact of the Turkestan General-Governorship’s education system on the current education system, offering solutions to the challenges that emerged as a result of this historical influence.
Keywords: -